Pengembangan E-Modul Dengan Bermuatan Karakter Mandiri Pada Materi Jenis-Jenis Usaha Dalam Bidang Ekonomi Kelas V Sekolah Dasar - Meilasari, Silvi; Kurniawan Barus, Yohannes; Ahadianto , Erif (University of Muhammadiyah Malang, 2024)
The lack of variety of innovative teaching materials in learning is a significant problem because it can cause students to feel bored and less enthusiastic and find it easier to concentrate when understanding the material. The impact is that student learning achievement, especially in social studies subjects covering types of business in the economic field, becomes low, while the level of student independence also decreases. This research aims to develop learning media in the form of e-modules for material on types of business in the economic sector by including elements of independent character. Its validity will be evaluated by experts and is expected to become a practical tool for teachers and students of class V SDN Kauman 02 Blitar City. It is getting an average score of 87.88% from material experts and an average score of 97.6% from media experts, with both categories being very valid. Meanwhile, the practicality test received an average score of 94.5% from teachers in the very practical category, 94.4% from small group assessments in the very practical category, and 95.4% from large group assessments in the very practical category. The effectiveness of the assessment on student learning achievement was evaluated through a t-test with the help of SPSS and produced a value of 0.000, which indicates that 0.000 < 0.05. Thus, it can be concluded that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. These results indicate an increase in student learning achievement in class V of SDN Kauman 02 Blitar City using e-module learning media, which is proven by the average of pre-test and post-test learning results. Overall, based on research findings, e-modules with material on types of business in the economic field are considered feasible by experts and practical to be applied in learning activities to improve student learning achievement.